2014
DOI: 10.1089/dia.2013.0246
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Response to Early Basal Insulin Treatment in Patients with Type 2 Diabetes—The EARLY Experience

Abstract: Identified predictors of greater HbA1c reduction, target goal achievement, and insulin dose needed may help to optimize the balance of benefits and risks with the use of insulin glargine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…Although only a small difference in mean HbA1c existed between groups at baseline, lower baseline HbA1c was still identified as a strong, independent predictor of response at 12 months. This finding appears to be consistent across patients initiating a range of insulin types . Higher FBG at baseline may also suggest a probable lack of response, athough the effect size is smaller and less clinically applicable.…”
Section: Discussionsupporting
confidence: 60%
“…Although only a small difference in mean HbA1c existed between groups at baseline, lower baseline HbA1c was still identified as a strong, independent predictor of response at 12 months. This finding appears to be consistent across patients initiating a range of insulin types . Higher FBG at baseline may also suggest a probable lack of response, athough the effect size is smaller and less clinically applicable.…”
Section: Discussionsupporting
confidence: 60%
“…The ORIGIN study [17], which is an example of early insulin treatment, showed that people receiving insulin glargine typically required fewer additional antidiabetic agents at the end of the study than those receiving standard care. Although we cannot find similar studies designed like ours, several studies showed that people with lower HbA1c levels at baseline, lower body mass index (BMI) and shorter duration of T2DM were more likely to achieve glycaemic targets [18][19][20].…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, in the ORIGIN study, early insulin therapy targeting HbA 1c < 6.5% reduced the risk of people with IGT progressing to T2DM, with a low risk of hypoglycaemia, only moderate weight gain and doses of insulin glargine consistent with those typically required during phase-III studies of T2DM. There is now a mass of evidence from clinical trials and long-term outcome studies that early introduction of basal insulin is effective at keeping glucose levels within the target range with doses < 0.4 U/kg, which are associated with a low risk of severe hypoglycaemia and only moderate, if any, weight gain [8,31,39]. In contrast, late basal insulin introduction requires a high dose of insulin glargine with excessive weight gain observed as an adverse effect [60].…”
Section: Resultsmentioning
confidence: 99%
“…The EARLY study investigated the use of basal insulin as second-line therapy following failure of metformin in 1438 people with T2DM [38,39], and demonstrated that early basal insulin therapy was safe and effective, with HbA 1c levels decreasing from 8.69% to 7.39% and a low rate of hypoglycaemia over 24 weeks. Subgroup analyses found that people with lower HbA 1c levels at baseline, lower body mass index (BMI) and/or shorter duration of T2DM were more likely to achieve glycaemic targets (HbA 1c < 7%) [39].…”
Section: Studies Investigating Early Insulin For Non-cardiovascular Bmentioning
confidence: 99%
See 1 more Smart Citation